USE OF ARTIFICIAL INTELLIGENCE IN ACCOUNTING AND ANALYTICAL PROCESSES (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The beginning of a new era has led to the emergence of new factors that impede the effective operation of enterprises. One of these factors is the exponential growth of the amount of data that needs to be processed and analyzed in order to make effective management decisions. This leads to the need to develop or search for a software product aimed at collecting, analyzing and systematizing a large amount of data, as well as performing relevant tasks based on them that artificial intelligence is capable of. The article is aimed at researching and revealing the potential of using artificial intelligence (AI) in the field of accounting. The main focus is on improving the efficiency of the enterprise, which is achieved by automating and optimizing various aspects of accounting work. On the basis of a thorough analysis of the works of foreign and domestic specialists, the theoretical aspects of the concept of artificial intelligence are distinguished on the basis of systemic, functional and information approaches. The directions of compliance of the accountant, which can be artificial intelligence, are identified, namely: processing of invoices, cost management, analysis of financial statements, management of payables and receivables, compliance with tax legislation and detection of fraud and risk management. Ways of using AI in processes of automation and optimization of processes, such as invoice processing, cost management, financial reporting analysis, control of accounts payable and receivable, ensuring compliance with tax legislation and fraud detection and risk management, have been identified. The artificial intelligence technologies for their purpose, which are the most used in the world, are presented. The sequence of actions in the identified needs in artificial intelligence and its outstanding volume is structured. The results of the study confirm the potential of AI to automate operations, increase productivity and accuracy in accounting, as well as reduce risks and improve audit efficiency. Key words: Artificial intelligence, accounting, analysis, accounting automation, accounting information systems, information systematization, management efficiency.
Keywords: Artificial intelligence, accounting, analysis, accounting automation, accounting information systems, information systematization, management efficiency